Implementation of Multicultural Education Cooperative Learning to Develop Character, Nationalism and Religious - Moch. Yusuf Efendi; Hsi Nancy Lien (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2021)
Races, ethnic groups, nationalities, and religions are considered important for implementing multicultural education.  the implementation of multicultural cooperative learning in an Islamic public primary school becomes a concern for this study. Therefore, this study aims to investigate the implementation of multicultural education in an Islamic Public School in Grobogan, Central Java. This study used descriptive qualitative, literature review, and a case study in an Islamic Public School. The findings of the study show that 1) multicultural education is a form of policy attention from the government and teachers about a variety of ethnicities and culture. multicultural education can be used as a strategic instrument to develop diverse ethnic and national cultures that can be a personal pride for the ethnic group. 2) Multicultural education is very suitable for a plural society such as Indonesia, which pays attention to the understanding of ethnic, religious, linguistic and ethnic differences, which requires new innovation democratic society. 3) Application of multicultural education in an integrated curriculum or integrated with other subjects. 4) The application of integrated multicultural education can use cooperative learning models. 5) The basis for efficient group formation is the formation of non-permanent groups with session agreements or face-to-face meeting agreements, which allow students to interact in turns with classmates. 6) Familiarization with the basis of the formation of varied groups in the cooperative learning model will develop an awareness that life now and later for students is no problem in adjustment.